Growth and dry matter of pitombeira seedlings under salinity levels and application of biofertilizer - Véras, Mario Leno Martins; Arruda, Rafaela da Silva; Alves, Lunara de Sousa; Melo Filho, José Sebastião de; Irineu, Toni Halan da Silva; Dias, Thiago Jardelino (Comunicata Scientiae, 2018)
Pitombeira is a native fruit tree from Amazon and is exploited in an extractive way. Currently, there is no commercial cultivation of this crop since there are no technologies for cultivation, propagation methods, fertilization and irrigation. In this context, the aim of this study was to evaluate growth and dry matter of pitombeira seedlings (Talisia esculenta (A. St.-Hill.) Radlk.) under salinity levels with or without bovine biofertilizer. The experiment was performed in a nursery at the State University of Paraíba (UEPB), Campus IV, in Catolé do Rocha, Paraíba, from September to December 2015. It was adopted a completely randomized design (CRD) with 10 treatments and 4 repetitions, in factorial arrangement 5 x 2, corresponding to 5 salinity levels: (0,8; 2; 4; 6 e 8 dS m-1) with or without bovine biofertilization. Plant height, stem diameter, number of leaves, leaf area, total leaf area, Dickson quality index, dry mass of root, stem, leaf and the whole plant were analyzed. The increase in salinity provides a decrease in growth and dry matter of pitombeira seedlings. The use of biofertilizers mitigates the harmful effects of salinity on pitombeira seedlings.